2010
DOI: 10.1186/1465-9921-11-144
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Snoring in school-aged children: environmental and biological predictors

Abstract: BackgroundHabitual snoring, a prominent symptom of sleep-disordered breathing, is an important indicator for a number of health problems in children. Compared to adults, large epidemiological studies on childhood habitual snoring and associated predisposing factors are extremely scarce. The present study aimed to assess the prevalence and associated factors of habitual snoring among Chinese school-aged children.MethodsA random sample of 20,152 children aged 5.08 to 11.99 years old participated in a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 36 publications
8
75
1
1
Order By: Relevance
“…These dose-response relationships have since been confirmed by others and, considering that the strength of the association appears to be stronger in younger children who spend more time at home or when maternal smoking is involved as opposed to paternal smoking, there is plausibility for a causal relationship linking exposure to cigarette smoking and habitual snoring [5,18,19,31,32]. These observations would further support the concept that other environmental pollutants may also contribute to the epidemiological characteristics of habitual snoring in children.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These dose-response relationships have since been confirmed by others and, considering that the strength of the association appears to be stronger in younger children who spend more time at home or when maternal smoking is involved as opposed to paternal smoking, there is plausibility for a causal relationship linking exposure to cigarette smoking and habitual snoring [5,18,19,31,32]. These observations would further support the concept that other environmental pollutants may also contribute to the epidemiological characteristics of habitual snoring in children.…”
Section: Discussionsupporting
confidence: 66%
“…The major risk factors enumerated for the presence habitual snoring include a positive family history of snoring, prematurity, obesity, ethnic characteristics, early life history of respiratory syncytial virus bronchiolitis, lower socioeconomic status, allergies, asthma and passive exposure to cigarette smoke [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][18]. More specifically, exposure to cigarette smoke increased the risk of habitual snoring in a dose-dependent fashion, such that the highest prevalence was found when both parents smoked [1,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitual snoring adalah mendengkur yang terjadi ≥3 kali dalam seminggu, sedangkan occasional snoring terjadi <3 kali dalam seminggu. 2,4 Habitual snoring dapat dibagi menjadi primary snoring, upper airway resistance syndrome (UARS) dan obstructive sleep apnea syndrome (OSAS). Primary snoring adalah mendengkur tanpa adanya apnea atau hipopnea, sedangkan UARS dan OSAS adalah mendengkur yang disertai gangguan pernapasan.…”
Section: Analisis Multivariatunclassified
“…[11] Two previous studies on pediatric patients demonstrated AR as a risk factor for habitual snoring. [12,13] Previous reports also showed that intranasal corticosteroid therapy and oral H1 receptor antagonists (second generation) improved the sleep quality. [9] Effects on Mood and Anxiety AR affects the patient emotions and patients felt tired, irritable and embrassed.…”
Section: Effects On Sleepmentioning
confidence: 99%